Discussion :: Problems on Numbers - General Questions (Q.No.15)
|Sunil said: (Jul 7, 2011)|
|The questions is for sum of two consecutive "even numbers"
So in your answer if x=1 then x+2=3 Both are odd numbers.
Therefore i think the solution may be as follows:-
Let the numbers be "2x" and "2x + 2".
Then, (2x + 2)^2 - 2x^2 = 84
The required sum = 2x + (2x + 2) = 42.
|Pratheep Msajce It said: (Jul 13, 2011)|
|The difference of the squares of the number is 84
(a-b)=2[it is difference between consecutive even no]
|Arafath said: (Jul 6, 2012)|
|How does x square become 4x. ?|
|Nivedha said: (Mar 17, 2013)|
|But, if we take x^2-(x+)^2 = 84,
The answer changes to 46.
Can anyone explain why they take (x+2)^2-x^2 = 84.
|Kranti said: (Jul 13, 2014)|
|@Nivedha ji, (x+2) is greater than x... and as it is for subtraction, he has taken larger number first, for getting a positive number.|
|Jack said: (May 14, 2015)|
|I think it should be.
(x^2) - (x+1)^2.
(x+x+1)(x-x+1) = 84 //Using a^2 -b^2 formula.
(2x+1)(1) = 84.
2x = 83.
x = 83/2.
Post your comments here:
Email : (optional)
» Your comments will be displayed only after manual approval.